Clinical psychologists' response to bereavement in adults with intellectual disability. Issue 2 (3rd May 2020) - Irwin, Lynn; O' Malley, Grace; Guerin, Suzanne
Abstract: This study aimed to explore the current clinical psychology approach in supporting bereaved adults with intellectual disability (ID). As the literature in this area is limited, report of real clinical practice may enhance our understanding of the usual role of clinical psychologists, and any factors which may shape this. Semi-structured interviews were carried out with six clinical psychologists and the resulting data analysed thematically. Findings identified the approach of participants when supporting bereaved adults with ID, as well as some factors affecting this, such as the impact of grief across support systems and the complexity of best practice in the absence of clear guidance. This absence of an evidence base to guide the clinical response in supporting bereaved adults with ID was identified as a source of professional concern for participants. Further guidance and resources, derived from high-quality research, are urgently required in order to address this issue.